Development of a portable labor-contraction monitor based on mechanomyography - Chaves, Juliana N.; Yehia, Hani C.; Martins, Henrique R. (Anais Estendidos do Simpósio Brasileiro de Computação Aplicada à Saúde (SBCAS); 2022: Anais Estendidos do XXII Simpósio Brasileiro de Computação Aplicada à SaúdeDO - 10.5753/sbcas_estendido.2022.222422, 2022)
Mechanomyography is a technique that measures the mechanical signal observed from the muscle surface during the contraction. It is expected to be a promising tool to evaluate uterine dynamics even though the uterus contraction is known to be involuntary. This study aimed to describe the development of a portable device based on mechanomyography to monitor uterine contraction. To assess the system was performed isometric contractions of the rectus femoris muscle with varying loads. The acquired data showed that the system could identify each contraction's onset, offset, and amplitude. The sensors and the system architecture proved to be a promising tool for the desired application.